Gratification Disorder as an Early Marker of Rett Syndrome: Two Pediatric Case Reports - Singhapakdi, Kanya; Maertens, Paul (Journal of Pediatric Neurology, 2020)
Gratification disorder (GD) is a form of stereotyped posturing with mechanical pressure applied to the genitalia without manual manipulation and is generally considered benign. Here, we describe two patients who exhibited GD. Both were later diagnosed with Rett syndrome via genetic sequencing. In both patients, GD preceded the onset of the hallmark hand stereotypies of Rett syndrome. We therefore conclude that GD is not as benign as previously assumed and in fact can be an early sign of Rett syndrome. Further studies are needed to evaluate the prevalence of GD in Rett girls with the MECP2 genotype.
Keywords: gratification disorder; Rett's syndrome; MECP2 gene